The logic towardess of the simbolic order (1992)
The logic towardess of the simbolic order, title of this article, is demostrated by reduction to the Petananaye legend of theirs structurants components: The Other big of the language, (the place of cede), the significants chain, the other (the reciprocal imaginary), the petition, the law, the desire, tha falic significant. These elements result of dismount to the legend by mean of J. Lacan's graphs, topologic resource. The reader will find that these components are transportated metonymically by the legend and so "that in" convoques the instauration of a stage: ritual, where it self produces the owner significant, S1, it is governed since towardess the simbolic order to the Ticuna group.